EMOTION RECOGNITION IN POLISH TEXTS BASED ON KEYWORDS DETECTION METHOD - Nowaczyk, Adrian Maciej; Jackowska-Strumiłło, Lidia (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
Dynamic development of social networks caused that the Internet has become the most popular communication medium. A vast majority of the messages are exchanged in text format and very often reflect authors’ emotional states. Detection of the emotions in text is widely used in e-commerce or telemedicine becoming the milestone in the field of human-computer interaction. The paper presents a method of emotion recognition in Polish-language texts based on the keywords detection algorithm with lemmatization. The obtained accuracy is about 60%. The first Polish-language database of keywords expressing emotions has been also developed.